2013
DOI: 10.3389/fneur.2013.00047
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia and Neurological Events: The Framingham Heart Study

Abstract: Background/objective: Transient global amnesia (TGA) is a temporary amnestic syndrome characterized by lack of other focal neurological deficits. Cerebrovascular disease, migraine and seizures have been suggested as underlying mechanisms. TGA may be a risk factor for cerebrovascular or other neurological events. We studied the relation of TGA, vascular risk factors, brain magnetic resonance imaging (MRI) indices of subclinical ischemia and neurological events in a community-based sample.Design/setting: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…[25][26][27] However, only a minority of our TGA patients were migraneurs (less than 30%) and did not show any difference with regard to intracranial hemodynamics, casting further doubts on the migraine-induced vasoconstriction/depolarization hypotheses of TGA. Considering the cerebrovascular hypothesis, similarly to a recent study by the Framingham group, 24 no significant differences between TGA and control patients were observed regarding the incidence of hypertension, diabetes, smoking, hypercholesterolemia, atrial fibrillation, and ischemic heart disease. Furthermore, the prevalence of extracranial and intracranial arterial stenosis among TGA patients was low and US, ultrasound; IMT, intima-media thickness; R.I., resistance index; PSV, peak systolic velocity; EDV, end diastolic velocity; MFV, mean flow velocity; VM, Valsalva maneuver; P.I., pulsatility index; MCA, middle cerebral artery; PCA, posterior cerebral artery; ACA, anterior cerebral artery; VA, vertebral artery; BA, basilar artery; N.S., not significant.…”
Section: Discussionmentioning
confidence: 85%
“…[25][26][27] However, only a minority of our TGA patients were migraneurs (less than 30%) and did not show any difference with regard to intracranial hemodynamics, casting further doubts on the migraine-induced vasoconstriction/depolarization hypotheses of TGA. Considering the cerebrovascular hypothesis, similarly to a recent study by the Framingham group, 24 no significant differences between TGA and control patients were observed regarding the incidence of hypertension, diabetes, smoking, hypercholesterolemia, atrial fibrillation, and ischemic heart disease. Furthermore, the prevalence of extracranial and intracranial arterial stenosis among TGA patients was low and US, ultrasound; IMT, intima-media thickness; R.I., resistance index; PSV, peak systolic velocity; EDV, end diastolic velocity; MFV, mean flow velocity; VM, Valsalva maneuver; P.I., pulsatility index; MCA, middle cerebral artery; PCA, posterior cerebral artery; ACA, anterior cerebral artery; VA, vertebral artery; BA, basilar artery; N.S., not significant.…”
Section: Discussionmentioning
confidence: 85%
“…The prevalence of risk factors in the large cohort corresponds to the distribution within the healthy, age-matched population (Quinette et al, 2006 ; Enzinger et al, 2008 ; Romero et al, 2013 ; Mangla et al, 2014 ). This applies to transient ischemic attacks, arterial hypertension, coronary heart disease, cardiac arrhythmia, subcortical arteriosclerotic encephalopathy, preexisting insults, lacunar stroke and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…18,51,52 Also, in a subset of 12 individuals from the Framingham Heart Study who had an episode of TGA, the investigators noted that these patients had a similar vascular risk factor profile and risk of future cerebrovascular events as stroke-free and seizurefree controls matched for Framingham Heart Study cohort, sex, and year of birth. 64 Recently, a study using a state registry including 4299 patients with TGA demonstrated that the stroke risk after the diagnosis of TGA (0.54%) was similar to that after the diagnosis of migraine (0.22%), was lower than the risk after the diagnosis of seizure (0.90%), and was much lower than that after the diagnosis of TIA (4.72%). 65 Risk of seizures in patients with TGA has not been demonstrated to be increased compared with other populations.…”
Section: Long-term Outcome In Patients With Tgamentioning
confidence: 93%